UFOS – UTP Food Ordering System - Venugopal, Thivnesh Kumar (2022)
The goal of the UFOS-UTP Food Ordering System project is to create an efficient food ordering system that can be used at UTP cafes. This system will improve student dining experiences while allowing café vendors to do daily operational tasks more quickly and easily. It's said that many UTP cafés still run their food ordering systems the old-fashioned way. Using the traditional way results in a lot of human error since the cafe's staff works with a large number of students; this problem will have a big effect on the vendors' profits. The project's goal is to provide UTP cafés a suitable food ordering system in order to address the issue.